2015
DOI: 10.1063/1.4936910
|View full text |Cite
|
Sign up to set email alerts
|

Transient β-hairpin formation in α-synuclein monomer revealed by coarse-grained molecular dynamics simulation

Abstract: Parkinson's disease, originating from the intrinsically disordered peptide α-synuclein, is a common neurodegenerative disorder that affects more than 5% of the population above age 85. It remains unclear how α-synuclein monomers undergo conformational changes leading to aggregation and formation of fibrils characteristic for the disease. In the present study, we perform molecular dynamics simulations (over 180 μs in aggregated time) using a hybrid-resolution model, Proteins with Atomic details in Coarse-graine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
108
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(117 citation statements)
references
References 144 publications
(346 reference statements)
9
108
0
Order By: Relevance
“…This observation of a major random coil along with a minor anti-parallel b-sheet conformation of aSyn is consistent with earlier reports. 54,55 A clear structural transition from random coil to b-sheet was observed for aSyn aer 37 hours of incubation under brillating condition ( Fig. 2A).…”
Section: Resultsmentioning
confidence: 93%
“…This observation of a major random coil along with a minor anti-parallel b-sheet conformation of aSyn is consistent with earlier reports. 54,55 A clear structural transition from random coil to b-sheet was observed for aSyn aer 37 hours of incubation under brillating condition ( Fig. 2A).…”
Section: Resultsmentioning
confidence: 93%
“…43 Here, from 1 H NMR spectroscopic results, we can nd that for inhibition of brillation, EGCG interacts with amino acid sites of Ile, Phe and Tyr which are different from Leu, His, Phe and Tyr for disaggregation of brils. Schulten et al 44 have found that residues from 36 to 55 in a-Syn adopt b-hairpin in b-sheet conformation by molecular dynamics simulation. Among those residues, Gly36, Leu38, Fig.…”
Section: Binding Sites Of Egcg To Amino Acids For Inhibition and Disamentioning
confidence: 99%
“…In particular, the A53T, A53E, and G51D mutations and SNCA gene triplications are associated with a more aggressive MSA-like clinical and pathological phenotype 45 (See Table 1 and Table 2 for details of the clinical and neuropathological features of SNCA mutations). Exactly why the codon 51 and 53 mutations in the SNCA gene lead to an MSA-like clinical and pathological phenotype is not known, but this is likely to be associated with the importance of this defined region and toxic gain of function of these protein changes ( Figure 1 ) 46 . From a clinical perspective, if there is any hint of a family history in patients with MSA, then the SNCA gene should be sequenced by using traditional Sanger 47 , gene panel, or exome sequencing and analysed for copy number changes 48 .…”
Section: Mutations and Copy Number Variation In α-Synucleinmentioning
confidence: 99%
“…In the nuclear magnetic resonance structure of SNCA, the negatively charged C-terminal tail remains flexible and disordered (based on Yu et al . 46 ). The positions of point mutations associated with Parkinson’s disease are indicated with arrows and in pink.…”
Section: Mutations and Copy Number Variation In α-Synucleinmentioning
confidence: 99%